2000
DOI: 10.1021/ma001228+
|View full text |Cite
|
Sign up to set email alerts
|

Importance of a Broad Composition Distribution in Polymeric Interfacial Modifiers

Abstract: The importance of the sequence distribution in a copolymer that is used as an interfacial modifier relative to the importance of its composition polydispersity is examined. Using Monte Carlo simulation, the microstructure of a copolymer is shown to have a greater influence on the ability of a copolymer to effectively strengthen a biphasic blend than the compositional polydispersity. Correlation to experimental studies and implications of these results on the design of polymeric surfactants are also noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In the literature, several contradictory results can be found regarding the influence of copolymer architecture on the blend interphase. For example, Dadmun et al demonstrated that random copolymers, with a tendency to crumple in on themselves, do not offer the opportunity for entanglements to occur, while architectures between random and block are able to penetrate along or across the interface and therefore significantly enhance the miscibility [30,31]. However, research on both polystyrene/poly(vinyl pyrrolidone)(PS/PVP) [64] and polystyrene/poly(methyl methacrylate)(PS/PMMA) [35,65] blends has shown that random copolymers can be very effective compatibilizers, due to crossing the interface multiple times, if the segments are long enough to entangle with the homopolymer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, several contradictory results can be found regarding the influence of copolymer architecture on the blend interphase. For example, Dadmun et al demonstrated that random copolymers, with a tendency to crumple in on themselves, do not offer the opportunity for entanglements to occur, while architectures between random and block are able to penetrate along or across the interface and therefore significantly enhance the miscibility [30,31]. However, research on both polystyrene/poly(vinyl pyrrolidone)(PS/PVP) [64] and polystyrene/poly(methyl methacrylate)(PS/PMMA) [35,65] blends has shown that random copolymers can be very effective compatibilizers, due to crossing the interface multiple times, if the segments are long enough to entangle with the homopolymer.…”
Section: Resultsmentioning
confidence: 99%
“…The block/segment distribution of a linear copolymer can vary from alternating to blocky to random, which plays an important role in its ability to enhance blend miscibility at the interface. Experimental and theoretical studies have confirmed that block copolymers are able to form different geometrical forms at the interface, starting from cylindrical for diblock copolymers and more isotropic with increasing number of blocks (crossing the interface many times) [30,31,32]. Furthermore, as the copolymer becomes more random or alternating, it can cover a more tangible part of the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Both theoretical and experimental studies , have shown that the diblock copolymer arranges itself across an interface in a cylindrical or dumbbell shape, crossing the interface once. As the copolymer becomes less blocky, the copolymer will begin to become more isotropic at the interface, crossing the interface many times. As the copolymer becomes more random and alternating, it will attain a pancake-type structure, covering a substantial area of the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need to experimentally clarify the relative importance of sequence distribution (i. e., microstructure) and composition distribution within a copolymer on its ability to improve the ultimate properties of biphasic polymer blends. [41] However, to make this distinction, there must be a more complete understanding of the relationship between the reactivity ratios of the monomers to the resultant composition and 'randomness' (sequence distribution) of the copolymers. This is required so that the evolution of the composition distribution and randomness distribution of a random copolymer can be controlled experimentally, which in turn, can lead to an understanding of the relative importance of these two distributions for various applications of random copolymers.…”
Section: Introductionmentioning
confidence: 99%